CIFOR’s research programme on conservation of tropical forest genetic resources - Boyle, T.J.B. (1996)
The research programme described is intended to comprehensively answer key questions relating to in situ conservation of genetic resources. Outputs will be in the form of models of how landscape processes affect genetic level processes, and in the form of management prescriptions or policy options. In the case of research on tools and methodologies, outputs will obviously be improved methods for assessment of genetic diversity. There are strong links to various elements of CIFOR's research agenda. The links to socio-economic research of CIFOR's Policy and Social Science scientists are obvious and have been emphasised throughout. In addition, there are links to the Forest Ecosystem Management initiative under the Natural Forest Management Division, especially to the activities dealing with measurement of biodiversity and impacts of human activity on biodiversity, and to various activities in the Research Support Division. These include efforts to model the human-forest interface, and the development of GIS technology.